Pengaruh Jenis Elektroda RD dan LB E6010 Terhadap Laju Korosi Sambungan Las SMAW Pada Baja Ringan Dalam Media Air Laut - Syam, Muh Yusril; Ainun Chandra Puspa Nigrum (Jurnal Teknologi Dan Riset Terapan (JATRA), 2025)
Mild steel is widely used in construction because it is lightweight and economical, but it is susceptible to corrosion, especially in marine environments with high chloride ion content. Shielded Metal Arc Welding (SMAW) welded joints are vulnerable due to microstructural changes and weld defects that accelerate damage. This study aims to analyse the effect of RD and LB E6010 electrodes on the corrosion rate of mild steel welded joints in seawater. The research method involved welding 1.5 mm galvanised steel using 70–90 amps of current with the stringer bead technique. The samples were then immersed for 21 days in seawater from Pagatan Beach, South Kalimantan, and tested using the weight loss method. The test results showed that the RD electrode had a corrosion rate of 0.83 mm/year, which was lower than that of the LB electrode at 1.11 mm/year. This difference was influenced by weld defects, where the LB electrode produced more porosity, slag inclusion, and pitting corrosion. Based on the ASTM G46 classification, both values fall into the moderate category. It can be concluded that the use of RD electrodes is highly recommended for light steel joining applications in marine environments, given their superior corrosion resistance.